Know how to manage personnel issues in the aftermath of COVID‐19 - O'Brien, Timothy (College Athletics and the Law, 2021)
College athletics departments, like so many employers, have learned how to adapt and continue to operate in a world dominated by COVID‐19. Initially, departments dealt with the cancellation of tournaments, championships, and seasons in the spring of 2020, which required focused effort, coordination, and immediate action.